2021
DOI: 10.3389/fmolb.2021.666623
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Potential of Secreted Modular Calcium-Binding Protein 1 in Low-Grade Glioma

Abstract: Background: Secreted modular calcium-binding protein 1 (SMOC1) belongs to a family of matricellular proteins; it was involved in embryo development, endothelial cell proliferation, angiogenesis, integrin–matrix interactions, cell adhesion, and regulation of glucose metabolism. Previous studies showed that the expression of SMOC1 was increased in some tumors. However, the prognostic value and the biological function of SMOC1 in tumor remain unclear.Methods: In this study, we explored the expression profile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Among these markers, 15 were PDR-based markers, 8 AMF-based markers, 10 MHL-based markers, 5 UMHL-based markers, 6 MHL3-based markers, and 16 UMHL3-based markers. These 60 MHB markers were annotated to 58 genes, and notably, 18 of these genes have previously reported to be associated with thyroid dysfunction or thyroid diseases, and 27 were involved in immune regulation (Additional file 1 : Table S2 [ 28 – 94 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Among these markers, 15 were PDR-based markers, 8 AMF-based markers, 10 MHL-based markers, 5 UMHL-based markers, 6 MHL3-based markers, and 16 UMHL3-based markers. These 60 MHB markers were annotated to 58 genes, and notably, 18 of these genes have previously reported to be associated with thyroid dysfunction or thyroid diseases, and 27 were involved in immune regulation (Additional file 1 : Table S2 [ 28 – 94 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, higher expression of SMOC1 correlated positively with a better prognosis in glioma patients. Wang et al also reported that SMOC1 was upregulated in low-grade gliomas (LGGs) and that higher SMOC1 expression correlated with a better prognosis in LGG patients [24]. Interestingly, SMOC1 expression correlated negatively with in ltration by B cells, CD4 + T cells, CD8 + T cells, macrophages and dendritic cells in LGGs, suggesting that SMOC1 may be associated with the tumor microenvironment of glioma [24].…”
Section: Discussionmentioning
confidence: 97%
“…SMOC1 in particular is a promising target as it acts downstream of RUNX2, a known master regulator of osteogenesis. While therapeutic upregulation of RUNX2 raises concerns regarding potential adverse effects including increased cancer and osteoarthritis risk [42,43], SMOC1 expression is instead associated with more favourable cancer outcomes [44,45]. Similarly to RUNX2, oncogenic properties are also described for other previously identified genes, e.g., EFNB2 [46].…”
Section: Discussionmentioning
confidence: 99%